From Berkman-archive, nr.XXVI. With dedication from Senya, dated; Paris, August 20, 1927, on the back. From left to right:Fléchine, Volin and Steimer (1927)
From Berkman-archive, nr.XXVI. With dedication from Senya, dated; Paris, August 20, 1927, on the back. From left to right:Fléchine, Volin and Steimer.